Effect of Group Form Poetry Therapy on Mental Status of Schizophrenic Patients - Masoud Fallahi-Khoshknab; Farid Fadaei; Masoud Karimlou; Hamid Asayesh (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Schizophrenia is one of the complex psychiatric disorders. Although the antipsychotic agent is the main treatment for this disorder, but psychological interventions are effective on clinical symptoms and poetry therapy as one of those interventions may be effective on psychosocial aspect of schizophrenia. The purpose of present study is investigation of poetry therapy effect on mental and behavioral state of schizophrenic patients. Materials & Methods: In this interventional and experimental study 29 schizophrenic patients were selected by sample of convenience from Razi psychiatry center and were assigned probability to poetry therapy group (n=14) and control group (n=15). For experimental group, poetry therapy was held in one hour session, twice weekly for 6 weeks. The brief psychiatric rating scale and behavioral problem scale were used as questionnaires. Statistical analysis of data was done by Independent T test and paired T test. Results: The findings showed that there was significant difference between mental and behavioral state of before and after intervention in poetry therapy group (P<0/001). There was no significant difference before and after intervention in control group (P=0/774). We found significant differences between poetry therapy and control group after intervention (P<0/05), but there was no difference between two groups before intervention (P=0/812). Conclusion: The study confirmed the effectiveness of poetry therapy on mental and behavioral state of schizophrenic Patients.